An integrated framework for assessing land-use/land-cover of Kelantan, Malaysia: Supervised and unsupervised classifications. Issue 1 (1st June 2022) - Yeo, L B; Wan Mohamad, W S N; Hasan, R; Othmani, N I; Abdul Hamid, N H; Ramlee, N; Yeo, O T S
Abstract: The change of land-use/land-cover (LULC) is inexorable to cater to the needs of the people, from a natural land use dominance to the built-up areas' dominance. Many geospatial studies have examined the LULC, yet the data used were not up-to-date. Hence, this paper proposes an integrated framework to assess the LULC by using the latest complimentary data of Landsat 8 from Earth Explorer-USGS, and subsequently processed in Geographic Information System application (ArcGIS 10.8) by executing two classification techniques: i) interactive supervised classification (ISC) and ii) Iso cluster unsupervised classification (ICUC). The study area is Kelantan, a state located in Peninsular Malaysia. Three hundred sampling points were randomly generated within the boundary of Kelantan to compare the classified map of 2021 with ground data using Google Earth Pro 7.3 and Google Street View. Results show that the ISC method presents an overall accuracy of 87.7% (K= 0.79, p≤0.001) compared to the ICUC method, with an accuracy rate of 67.7% (K= 0.47, p≤0.001). ISC method with the proposed integrated framework can be viable techniques to assess LULC and can be used to study the change of LULC periodically. Thus, it helps stakeholders make better decisions in resource planning and distribution, especially in Kelantan, where the natural resources are rich.